Relation Between of Nutritional Status and Vitamin C Conditions with Hemoglobin Levels in Anemic Pregnant Women in The Working Area of Pauh Public Health Center, Padang City - Nurul Badriyah; Hasmiwati; Desmiwarti (Institute of Computer Science (IOCS), 2021)
Hemoglobin (Hb) level is a specific indicator for determining anemia in pregnant women. One of the factors that triggers anemia in pregnancy, namely nutritional status and vitamin C levels. The purpose of this study was to determine the relationship between nutritional status and vitamin C levels with hemoglobin levels in anemic pregnant women in the working area of Pauh Public Health Center, Padang City. This study is an observational study with cross sectional design on 57 pregnant women with anemia in trimesters II and III with consecutive sampling technique. The research was conducted at the Pauh Health Center and the Biomedical Laboratory of the Faculty of Medicine, Universitas Andalas, from March to May 2020.Nutritional status was checked by measuring upper arm circumference (LILA), vitamin C levels were checked by ELISA method and Hb levels was by hematology analyzer. Data analysis used Pearson correlation test and Spearman correlation test. The results showed that the average nutritional status was 23.68 ± 1,810 cm, the vitamin C level was 21.13 ± 12.502 ng/mL, and the Hb level was 9.85 ± 0.865 gr/dL. There was a significant relationship between nutritional status and Hb levels in anemic pregnant women with a value of p = 0.012 and (r = 0.330) and there was no relationship between vitamin C levels and Hb levels in anemic pregnant women with p = 0.177 and (r = -0.168 ). The conclusion is that there is a relationship between nutritional status and Hb levels, but there is no relationship between vitamin C levels and Hb levels in anemic pregnant women in the Pauh Public Health Center, Padang City.